2023
DOI: 10.1155/2023/4110344
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Posner‐Schlossman Syndrome Patients in China

Abstract: Background. To explore the clinical characteristics of Posner-Schlossman syndrome (PSS) patients in China, especially the risk factors associated with the dynamic changes of corneal endothelial cell (CEC) density and retinal nerve fiber layer (RNFL) thickness during the course of the disease. Methods. In this retrospective cohort study, patients consequently suffering from PSS were recruited. Patients data including gender, age of onset, frequency of attack, and disease duration. We performed detailed ophthalm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 32 publications
0
3
1
Order By: Relevance
“…Accordingly, the average course of disease in our patients was 3.39 ± 6.56 years, while was significantly shorter than 9.5 ± 10.4 years in Gao's study (36). The selection bias and a relatively small sample size may be responsible for the different results in our study from previous studies (5,36). A longitudinal study with larger sample size is needed to further investigate the influencing factors on the progression of PSS.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations
“…Accordingly, the average course of disease in our patients was 3.39 ± 6.56 years, while was significantly shorter than 9.5 ± 10.4 years in Gao's study (36). The selection bias and a relatively small sample size may be responsible for the different results in our study from previous studies (5,36). A longitudinal study with larger sample size is needed to further investigate the influencing factors on the progression of PSS.…”
Section: Discussioncontrasting
confidence: 60%
“…Jap et al ( 5 ) held that disease duration was the only factor leading to glaucomatous optic nerve injury in PSS. Gao et al ( 36 ) showed that both the duration of the disease and the frequency of attacks affected the progression of PSS. However, we could not find the correlation between disease duration or disease frequency and the wiVD or wiPD in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been hypothesized that mild inflammation does keep recurring, which goes undetected, leading to optic nerve damage and retinal nerve fiber layer (RNFL) thinning. [ 36 ] Therefore, it can be rationalized that continuation of glaucoma medications is important in patients who show glaucomatous optic nerve damage, those with a large cup: disc ratio, or focal thinning of neuroretinal rim,[ 10 24 ] with some even advocating to continue medications in those at risk of NAION, as cases of NAION post PSS have been reported. [ 37 ]…”
Section: Discussionmentioning
confidence: 99%